THE NATURE OF PROFESSIOGRAPHY, HISTORY OF ITS FORMATION - Mamatov Ravshanbek Rustamovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the second half of the 1920 s, Russian psychotechnicians developed the principles and methods of professional activity in fast pictures. As a result of the generalization of the same studies, a special concomitant in psychotechnics led to the formation of a professional. The essence of this approach – the “image of professions” as a whole includes the study of professionalism, psychological description and design of the profession.